2008
DOI: 10.2106/jbjs.f.01351
|View full text |Cite
|
Sign up to set email alerts
|

Displacement/Screw Cutout After Open Reduction and Locked Plate Fixation of Humeral Fractures

Abstract: The use of locking plates in the surgical treatment of proximal humeral fractures is associated with an unexpectedly high rate of screw cutout and revision surgery, especially in patients older than sixty years who have a three or four-part fracture. The indications for open reduction and internal fixation in these patients require continued analysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
318
2
25

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 435 publications
(356 citation statements)
references
References 21 publications
11
318
2
25
Order By: Relevance
“…8 The goal of surgery is obtaining and maintaining satisfactory reduction in order to allow early motion, achieve healing and restore function. 1 Several authors have presented short term results with mixed outcome. 2 Frankhauser et al reviewed their experience of 28 patients with 29 proximal humerus fractures treated with locking proximal humeral plate.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…8 The goal of surgery is obtaining and maintaining satisfactory reduction in order to allow early motion, achieve healing and restore function. 1 Several authors have presented short term results with mixed outcome. 2 Frankhauser et al reviewed their experience of 28 patients with 29 proximal humerus fractures treated with locking proximal humeral plate.…”
Section: Discussionmentioning
confidence: 99%
“…1 Their overall incidence has been reported to be 73 cases per 100, 000 individuals per year. 2 As indicated by Cofield , areas still in question include radiographic diagnosis, operative or non operative treatment, consideration of patient age in treatment decision making, surgical approach, fracture fixation or hemiarthroplasty, type of internal fixation, and rehabilitation protocol.…”
Section: Introductionmentioning
confidence: 99%
“…Owsley et al reported a significant increase of complication rate in their elderly patients. 23 In addition, a multicenter trial found a relative risk increase of 3.3 of implant-related complications in the their elderly population, and the number of postoperative complication was directly corollary with functional outcome. 7 Our study does contain a number of limitations, most notably its small sample size and retrospective nature.…”
Section: Discussionmentioning
confidence: 99%
“…Second, the decision to indicate patients for surgery and to use the locking plate was at the discretion of the treating surgeon, as were the number of screws used in the humeral head, which may have potentially affected our complication rate. Other investigators have noted the number of screws in the head may influence cutout, fixation, fracture healing, or perfusion of the humeral head [21]. We only analyzed patients who underwent surgical treatment with a locking plate and did not include patients who underwent arthroplasty or other fixation methods.…”
Section: Discussionmentioning
confidence: 99%
“…Intra-articular screw perforation was our most prevalent complication, and it can arise because of improper hardware placement due to poor intraoperative imaging, screw migration/ implant shifting, or collapse of the subchondral bone onto the stationary hardware [9]. The incidence of this complication is well documented in the current literature and ranges from 5% to 23% [8,9,14,18,21]. This complication can cause substantial injury to the glenohumeral joint, require reoperation, and lead to permanent loss of joint function [29].…”
Section: Discussionmentioning
confidence: 99%